Optimisation of Retrofitted Steel Bridge Girders Subjected to Fatigue Loading. Issue 3 (16th September 2019) - Mirza, Olivia; Fieck, Syhra; Pathirana, Sameera; Mashiri, Fidelis
ABSTRACT: The RMS is responsible for the upkeep of more than 5600 bridges within NSW, with an estimated replacement cost of $15.35 billion (1). Of these bridges, it is estimated that 12% are approaching 70 years of service life and 50% are more than 40 years old (1, 2). As a result, a significant amount of bridges are structurally deficient, as they were never designed for the traffic loads or frequencies they are subjected to today (2). The increased weight and frequency of traffic has a serious impact on the fatigue life of steel bridges, and if appropriate retrofit methods are not implemented, then it inevitably becomes necessary to replace the bridge at great expense. This study examined the suitability of bolted retrofit plates to remediate and prevent fatigue fractures in the tension flange of bridge girders, focussing on the effects that the gap between the bolt and bolt hole has on the development of composite action. This was achieved by carrying out a parametric study on various bolt hole sizes and examining the effects on girder stiffness and ultimate load carrying capacity. It was found that bolt hole size has significant impact on how early in loading, composite action is initiated, and how much the girder needs to deflect before composite action is fully developed. The results showed that a bolt gap greater than 0.5mm could have significant impact on the overall performance of the girder, both in terms of serviceability and ultimate load carrying capacity.